2021
DOI: 10.3390/app11177879
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Asymmetry and Stress in Macaca fuscata: Does Captivity Affect Morphology?

Abstract: Fluctuating Asymmetry (FA) in morphology is used as a proxy for developmental instability in response to stress factors. FA has important implications for understanding the impact of differential environments and stressors on the skeletal phenotype. Here, we explore FA in the mandibular morphology of wild and captive Macaca fuscata to detect differences induced by the captive environment. We use two different approaches in Geometric Morphometrics to characterise the degree and patterns of FA and Directional As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…These results support earlier findings that sex has little influence on FA in the Cayo Santiago macaque population (Hallgrímsson, 1999), which aligns with many studies on FA across animal clades (Caccavo et al, 2021;Castilheiro et al, 2022;Hallgrímsson, 1993;Hopton et al, 2009;Landi et al, 2021;Van Dongen, 2015;Wauters et al, 1996) but does not align with a handful of studies in humans (Schlager & Rüdell, 2015), gorillas (Romero et al, 2022), olive baboons (Romero et al, unpublished data), lizards (Simbula et al, 2021), and shrews (Badyaev et al, 2000). These studies used a variety of data collection methods (e.g., caliper measurements, 2D photographs, 3D landmark patches) and measured different body components (e.g., mandibles, crania, femoral pores), making consistency impossible and comparisons relatively difficult.…”
Section: Sex and Fluctuating Asymmetrysupporting
confidence: 91%
“…These results support earlier findings that sex has little influence on FA in the Cayo Santiago macaque population (Hallgrímsson, 1999), which aligns with many studies on FA across animal clades (Caccavo et al, 2021;Castilheiro et al, 2022;Hallgrímsson, 1993;Hopton et al, 2009;Landi et al, 2021;Van Dongen, 2015;Wauters et al, 1996) but does not align with a handful of studies in humans (Schlager & Rüdell, 2015), gorillas (Romero et al, 2022), olive baboons (Romero et al, unpublished data), lizards (Simbula et al, 2021), and shrews (Badyaev et al, 2000). These studies used a variety of data collection methods (e.g., caliper measurements, 2D photographs, 3D landmark patches) and measured different body components (e.g., mandibles, crania, femoral pores), making consistency impossible and comparisons relatively difficult.…”
Section: Sex and Fluctuating Asymmetrysupporting
confidence: 91%
“…Here, we suggest PFEH could be used as a marker of anthropogenic impact, for which there is growing evidence of changes in diet, behavior, and social structures, e.g., [64]. PFEH could also be useful alongside other studies on nutrition and population health, such as previous investigations using urinalysis and fecal analysis [59,65] and morphological comparisons [66,67]. Primatological studies have also shown how the feeding behavior and ranging patterns of Yakushima macaques have changed alongside human landscape alterations, both daily and across seasons, e.g., [68].…”
Section: Discussionmentioning
confidence: 98%
“…Studies on the postcranium suggest the skeleton is not as plastic in size or shape in response to captivity (Bello‐Hellegouarch et al, 2013; Lewton, 2017; Turner et al, 2018), although there is some evidence for modest changes in limb proportions in response to translocation and functional joint surfaces in response to substrate use patterns more broadly (Clarke & O'Neil, 1999; Kimura & Hamada, 1996; Paterson, 1996; Simons et al, 2019; Turley & Frost, 2018; Venkataraman et al, 2013). Changes in the cranium attributed to perturbations in social environment or functional uses of craniomandibular structures due to captivity have been implicated in Japanese macaques ( M. fuscata ) and big cats ( Panthera ), as well as the development of secondary sexual characteristics in male mandrills ( Mandrillus ; Hartstone‐Rose et al, 2014; Kamaluddin et al, 2019; Landi et al, 2021; Saragusty et al, 2014; Singleton, 2012). Given the large and useful skeletal samples derived from semi‐free ranging captive populations like Cayo Santiago, more studies should explore the effects of provisioning and captivity on skull shape, not only size.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that captivity can provoke morphological responses in craniomandibular shape despite greater theoretical developmental and evolutionary constraints than on the postcranium, suggesting cranial morphology can respond to rapid environmental shifts (e.g., Buck et al, 2010; Kamaluddin et al, 2019; Marroig & Cheverud, 2010). As captive populations are subject to myriad environmental changes that may have an influence on morphology (e.g., Kamaluddin et al, 2019; Kimura & Hamada, 1996; Landi et al, 2021; Singleton, 2012), we investigate two translocated captive populations of M. mulatta to explore how cranial morphology may respond to rapid environmental shifts in general, encompassing climatic, dietary, and sociosexual factors.…”
Section: Introductionmentioning
confidence: 99%